Factors That Influence The Incident Of Stunting In Infants And Toddler - Utomo, Deddy; Baequni, Ahmad; Himawan, Fatchurrozak; Hartono, Mardi (Jurnal Ilmu Kesehatan, 2024)
Abstract Stunting is a serious public health problem in Indonesia, with a prevalence reaching 27.7% in 2021. The problem of stunting is considered to disrupt human resource potential and is related to health levels, even child mortality, so it is important to resolve it. This research aims to identify factors related to the incidence of stunting in infants and toddlers in Indonesia. The factors studied in this research include birth weight and family income. The study was designed to use a cross-sectional research approach. In this study, the dependent variable is the incidence of stunting and the independent variables include: factors such as birth weight and family income are evaluated at the same point. The research results show that the birth weight of the baby and the incidence of stunting show a significant influence, with a significance value of 0.001 (< 0.05), as well as the family income variable showing a significant influence on the incidence of stunting with a significance value of 0.003 (< 0.005). The conclusion is that there is a significant influence between birth weight and family income on the incidence of stunting. Keywords: Stunting, birth weight, family income